Effect of acupuncture on the molar bite force in women with chronic neck pain - Odinê Rêgo Bechara; Marcelo Palinkas; Selma Siéssere; Simone Regalo; César Bataglion (Universidad de Concepción., 2023)
Objetive: To investigate the maximum molar bite force in women with chronic neck pain after treatment with acupuncture. Materials and Methods: Twenty-three women with chronic neck pain participated. Dynamometer was used to measure the right and left maximum molar bite force. Dong Bang acupuncture needles - 0.25 mm x 30 mm was inserted into the integumentary tissue. Treatment was 10 sessions, each 30 minutes long and twice a week. Results: The right (p = 0.01) and left (p = 0.004) molar bite force was assessed after treatment with acupuncture, and showed increased occlusal strength. Conclusions: This study suggests a functional improvement in the stomatognathic system in women with chronic cervical pain after treatment with acupuncture. However, it is important to note that further research is needed to fully elucidate the long-term effects and potential clinical implications of these findings in the field of pain management and rehabilitation.